Catalytic Oxidation of Tartrazine in Aqueous Solution Using a Pillared Clay with Aluminum and Iron - Ángel David Gálvez-Serna; Iván Fernando Macías-Quiroga; Gloria Inés Giraldo-Gómez; María Teresa Dávila-Arias; Nancy Rocío Sanabria-González (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
In this work, pillared bentonite with Al−Fe (Al−Fe−PILC) was synthesized and used as a heterogeneous Fenton-like catalyst in the oxidation of tartrazine azo-dye in an aqueous solution. The modification of bentonite with the Al-Fe mixed system in a concentrated medium, with ultrasound assisted intercalation was carried out, and the obtained catalyst was characterized by XRF, XRD, and N2 adsorption at 77 K. The oxidation of tartrazine with Al−Fe−PILC, using different amounts of H2O2, expressed as a multiple (1, 3, 6, and 9) of a stoichiometry amount required to completely oxidize the dye was evaluated. The reaction of catalytic wet peroxide oxidation (CWPO) of the dye with 400 mg of Al−Fe−PILC and 6 times the stoichiometric amount of H2O2 at 25 °C, reached 98.2±1.8% of decolorization, 51.9±1.9% of TOC removal and 71.5±1.8% of TN removal. Results of this study show that the oxidation of tartrazine increased with the amount of H2O2 up to a certain limit. This oxidation process can be considered as an alternative for treating wastewater containing azo-dye because the reaction takes place under mild experimental conditions (room temperature and atmospheric pressure). Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA  License (https://creativecommons.org/licenses/by-sa/4.0).